Non-perturbative solution of the dual BBGKY hierarchy for hardsphere fluids - Gerasimenko, V.I.; Gapyak, I.V. (Доповіді НАН України, 2023)
The communication presents a rigorous description of the evolution of observables of many colliding particles. For expansions representing a solution of the Cauchy problem of the dual BBGKY hierarchy representations of their generating operators are established.